Mobile Interaction Meets AI Tutoring: Using ChatGPT-4o to Boost Speaking Skills in EFL Classrooms - Behforouz, Behnam; Al Maqbali, Abdullah; Al Ghaithi, Ali; Poorghorban, Afrooz (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The primary aim of this study was to implement the usage of ChatGPT-4o as an interactive artificial intelligence (AI) tool in the language learning context to measure its impact on the speaking skills of English as a Foreign Language (EFL) learners. To collect the required data, 62 Omani EFL learners with an intermediate level of English proficiency were randomly and equally divided into a control and an experimental group. To ensure the homogeneity of students in terms of speaking abilities, a pre-test was initially conducted. During the one-month treatment period, both groups received regular in-class training daily; however, the experimental group was engaged in the interactive and premium version of ChatGPT-4o outside of the classroom for extra practice and feedback. After the treatment, a post-test was administered to compare the performance of learners within their groups and in comparison with their counterparts. The findings of the study revealed that students’ scores in both groups increased from pre- to post-test, which could be associated with the daily training; however, the performance of the experimental group in the post-test was significantly better than the control group, and this could be linked to the use of ChatGPT-4o as the facilitator of learning. Additionally, the analysis of the scores among experimental group participants revealed that task response (26.2%) and grammar (26.2%) received the highest increase after using AI, followed by vocabulary (24.6%) and pronunciation. The study’s results are helpful for teachers, students, and institutions.